The value of immunotherapy in head and neck cancer. (2nd January 2019) - Manca, Paolo; Raez, Luis E.; Salzberg, Matthew; Sanchez, Jorge; Hunis, Brian; Rolfo, Christian
ABSTRACT: Introduction : Head and neck squamous cell carcinomas (HNSCC) previously had limited treatment options once patients had progressed on systemic chemotherapy. With recent advances, immunotherapy now plays an important role in the treatment of advanced disease with improved outcomes as compared to cytotoxic chemotherapy. Areas covered : This article reviews the effects of the immune system and how it influences the development and response to HNSCC therapy. We additionally provide a summary of immunotherapy treatments available as well as their applicable clinical trials that led to their approval. Expert Commentary : The challenges that need to be addressed in order to maximize the benefits of immunotherapy in HNSCC are the selection criteria for immune checkpoint inhibitors and the optimization of combination regimens of immunotherapeutics or chemo-immunotherapy. Furthermore, there remains to be a lack of knowledge in how to incorporate molecular biomarkers as predictors of response to HNSCC immunotherapy.